Impact of introduction of the anti-female genital mutilation law on the practice of female genital mutilation in Garissa County, Kenya - Derowa, Yasmin H.; Gitonga, Eliphas; Otieno, George; Yoos, Alison; Jisuvei, Clayton S. (International Journal Of Community Medicine And Public Health, 2021)
Background: Female genital mutilation (FGM), is a social traditional practice performed by cutting parts of the external female genitalia. Garissa county in north eastern Kenya has the highest prevalence of FGM in Kenya at 94%. This practise was illegalised in Kenya in 2011. The aim of the study was to assess the successes of anti-FGM programs in Garissa County. Methods: This was a cross sectional study involving 108 participants of both genders and different age groups. Questionnaires were used in data collection. Obtained data was analyzed using SPSS version 25. Chi square was used to compare characteristics between female participants who had undergone FGM and participants not circumcised. Results: Of the 108 participants, 53.7% were females. The median age of participants was 23 years [Interquartile range (IQR])15-40]. The prevalence of FGM was 62% with the mean age at circumcision being 8.34 years (SD=2.69 years). Being of Muslim faith was associated with practice of FGM (p<0.001). There was high level of awareness of the anti-FGM law among youths at 84%. Two thirds of participants did not support FGM. Excision was the main type of FGM practiced. Among those circumcised, 14.7% were circumcised by trained nurses. Conclusions: Introduction of the anti-FGM law, and its advocacy by NGOs has led to a reduction in the practice of FGM in Garissa county. There is an increase in the medicalization of FGM in Garissa with evidence of the practice going underground. This study recommends NGOs to have a clearer focus on the method chosen for use in advocating for the abandonment of FGM.